Merit Rating - Chartier, Roger; Fuerstenthal, A. H. (Relations industrielles / Industrial Relations, 1952)
SummaryThe Authors are using both the theoretical and the practical approach in their discussion of various aspects of Merit Rating. After stating what Merit Rating is, why, when and on what it is used, how it works, and by whom and on whom it is applied, the Authors describe at length, and with illustrations, the different steps of a new method of service appraisal which they have devised on the basis of a one-year experience with hundreds of clerical workers in a big Canadian public utility concern abroad.